Ayurvedic Management of Insulin Resistance-related Conditions in Polycystic Ovary Syndrome - Anshul Chauhan; Dinesh Badwal; Pooja Arya; Ashish Mehta (Journal of Ayurveda)
Introduction:Polycystic ovary syndrome (PCOS), an endocrine-related metabolic disorder comes with hormone-related disturbances. Insulin resistance (IR) is the main pathophysiology of PCOS. IR results in atherosclerosis and obesity (~Medo Roga). Main Clinical Finding:A 24-year-old female patient presented with complaints of disturbed menstruation, excessive weight gain, and laziness associated with increased sleep and sweating for 5 years. Diagnosis:On the basis of ultrasound (abdomen) and hematological findings, the patient was diagnosed with PCOS with IR-related conditions. Interventions:After two sittings of Virechana (~therapeutic purgation), a workout at gym for 1 month was advised. Follow-up was done after every 2 months of therapeutic purgation till 6 months. Outcomes:Triglyceride changed from 155 to 90 mg/dL, total cholesterol from 232 to 162 mg/dL, high-density lipoproteins (HDL) cholesterol from 43 to 44 mg/dL, very low-density lipoprotein from 31 to 18 mg/dL, low-density lipoproteins (LDL) 158–100 mg/dL, total cholesterol/HDL ratio changed from 5.39–3.682, LDL/HDL from 3.674–2.273, and weight from 96 to74 kg. Conclusion:The outcomes of this case suggest that therapeutic purgation karma can be efficacious in dealing with IR-related conditions in PCOS.